Long-term transplant outcomes after allogeneic hematopoietic transplant in pediatric patients with hematological malignancies are influenced by severe chronic graft vs. host disease and immune reconstitution - Molina, Blanca; González-Vicent, Marta; Lopez, Ivan; Pereto, Alba; Ruiz, Julia; Ramirez, Manuel; Díaz, Miguel A. (Frontiers in Pediatrics, 2022)
Long-term follow-up studies are crucial to ensure surveillance and intervention for late complications after allogeneic stem cell transplantation but they are scarce in the pediatric population. The study was aimed to analyze risk factors for long-term transplant outcomes. We report a landmark analysis of 162 pediatric patients receiving an allogeneic transplantation between 1991 and 2016, and surviving at least 12 months after transplant. With a median follow-up time of 10 years, transplant outcomes are negatively affected by poor immune T-cell reconstitution and severe chronic GVHD. Conclusions Transplant strategies should be aimed to reduce the risk of severe cGvHD. Immune reconstitution surveillance may help clinicians to better dealing with late transplant complications.